Physico-chemical parameters of Titrigachhi Daha - Chhetry, Damodar Thapa; Pal, Joydeb (Nepalese Journal of Biosciences, 2013)
This paper deals with the physico-chemical parameters of the Titrigachhi daha. The maximum air temperature was recorded in rainy season but the water temperature was maximum in summer and lowest in winter season. Transparency, pH, dissolved oxygen, total alkalinity, total hardness were maximum in winter season. Free carbondioxide, chloride and biological oxygen demand were maximum in summer season. The minimum transparency, total alkalinity, total hardness and chloride were recorded in rainy season. Dissolved oxygen and pH, was minimum in summer season. The minimum carbondioxide and BOD were recorded in winter season. Air temperature, water temperature, free carbondioxide, and biological oxygen demand showed positive and significant correlation with each other. Similarly, transparency, pH, dissolved oxygen, total hardness showed positive and significant correlation with each other. Total alkalinity showed positive and significant correlation with chloride. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7465 Nepalese Journal of Biosciences 1: 19-25 (2011)